Solving a Vehicle Routing Problem with Time Window for Transportation Service Planning for Elderly People: A Case Study of Hatyai District Songkhla Province - Lateh, Alawee; Suthammanon, Sakesun; Sirivongpisal, Nikorn; Tehyo, Muhamad (Princess of Naradhiwas University Journal, 2019)
In this paper, we provide some insights to this problem called Home to Hospital Transport Planning (HHTP) for Elderly who need to go to the hospital without personal car. In other word, Door to Door service with timetable is employed to reduce transportation cost. The case study is Hatyai District, Songkhla Province, Thailand. The number of elderly people visiting the hospital for doctor appointment by themselves are almost 150,000 trips per year. In this view point we use an algorithm with standard VRPTW problem in ArcGIS 10.2 software to solve this problem. The result shows that the distance can be decrease 65.64 percent from 2,619,334.80 km./year to 657,000 km./year, and we compare the various types of transportation currently in Hatyai District with HHTP to shows different types of services, schedules, coverage, and fares.